German and Polish case rolls with regard to their interference - Sadziński, Witold (Acta Universitatis Lodziensis. Folia Germanica, 2017)
A contrastive study can be designed as a presentation or investigation procedure. In the present contribution, they are used in a complementary way by additionally examining the already numerically divergent pure cases of German and Polish with respect to their differing syntactic roles. Particular attention was paid to the individual language-specific case change – preferably in the active-passive diathesis, under the influence of negation, and in relation to numbers / measures and quantities.